Analysis of technical and economic indicators for maize culture in the period 2007-2017 - Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Maize, original from America, ranks third in the top of cereal crops as importance and ranks second in the international top, after wheat cultivation, these positions being acquired due to a series of particularities I presume: high production capacity, wide area spreading, ecological elasticity and the fact that it is a good precursor for most crops. The present study analyzes, at national level, both the technical indicators (cultivated area, average production) and economic indicators (prices, subsidies granted per hectare, economic balance) for maize crop in the period 2007-2017. By using the methods of statistical analysis, we will follow the evolution of the statistical data series studied, the purpose of the paper being to highlight both the technical and economic aspects of the studied culture, the dynamics and the importance of the maize culture referring to the demand of the internal market.
Keywords: Q10; Q11; Q18; 330; indicators; average production; price; economic balance